A rare case of Bowen's disease of the nipple: Literature review and management pathway. Issue 6 (24th March 2020) - Liang, Derek G.; Soliman, Bishoy; Cha, Jeon
Abstract: Introduction: Bowen's disease or squamous cell carcinoma in situ is a precursor malignant neoplasm restricted to the epidermis. Clinically and histologically, Bowen's disease of the nipple can resemble Paget's disease. It is crucial to differentiate between the two with immunohistological staining in order to provide the appropriate treatment. This review of Bowen's disease of the nipple will examine the diagnostic and treatment modalities previously used. We also present our own case of Bowen's disease of the nipple and propose a clinical pathway for this rare disease process. Methods: A review of published literature using MEDLINE, PubMed, and Google Scholar revealed seven articles were identified with a total of eight cases of Bowen's disease of the nipple. Results: Treatment modalities varied within the literature. This ranged from photodynamic therapy to simple mastectomy and sentinel lymph node biopsy. Standard surgical margins are inadequate for Bowen's disease of the nipple, as it has been shown to spread along the lactiferous ducts. Our case is of a 57‐year‐old female with Bowen's disease of her right nipple, confirmed through immunohistological staining. Wide local excision with immediate full‐thickness skin graft reconstruction was performed and is now disease‐free with a healed graft. Conclusion: There is no accepted management pathway for Bowen's disease of the nipple. We propose a treatment algorithm that involves immunohistological staining to diagnose Bowen's disease of the nipple. This would then be followed by a wide local excision, complete nipple excision including underlying lactiferous ducts and glandular tissue and subsequent reconstruction.